Suffering and wisdom - Schmitt, Raymond F. (Journal of religion and health, 1981)
Suffering is frequent in life, often ensuing when a wished-for state cannot be realized. One common response to suffering is mourning. Mourning may take problematic forms, and this can lead to chronic denial or embitterment or despair or stagnation. On the other hand, mourning may occur in such manner as to facilitate meaning in life, empathy, caring, and perspective. One's "myths" and beliefs often affect the mourning process and may themselves be influenced by that process. Different myths accompany or influence different identity patterns and life-styles. The core concepts of religion are often associated with certain myths and beliefs that may inspire meaning and courage, caring and wisdom.